PERAN KANTOR IMIGRASI SEMARANG DALAM PENAGGULANGAN TINDAK PIDANA PERDAGANGAN ORANG - Pujiyono, Amiek Soemarmi, Herdian Eka Putravianto, (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Human trafficking previosly was known with the term of slavery. However, along with the times and the developing of different modes of crime that also influence to the rises of new crimes, the term of slavery is never used again and replaced with the term of trafficking in persons or human trafficking. Human trafficking can take victims anyone from adults to children, both male and female. Criminal offense of human trafficking is a crime that can be regarded as transnational crime, because its scope not only inside the territoryof Indonesia but to be outside the territory of Indonesia. The legal research was conducted to determine how far the role of law enforcement agencies in countermeasures criminal offense of human trafficking. The approach method used is the approach method of juridical sociological or empirical. After analyzing secondary data relating to the policy of the law in criminal offenses human trafficking and then was conducted research at the Immigration Semarang Office, as institutions that handling criminal offenses of immigration. The goal is to describe the phenomena occurring in the handling of criminal offenses human trafficking, it can be in the form of helpful in management of passport and visa to be used on the way to inside or to outside of Indonesia, as well as assist in the repatriation of TKI/TKW were accommodate at the Embasy who had been deported.